Relationships between sacral, lumbar and thoracic spine position and trunk mobility in the sagittal plane in young adults - Wódka, Katarzyna; Michalczyk, Alicja; Jankowicz-Szymańska, Agnieszka (Health Promotion & Physical Activity, 2022)
Aim of the study: The aim of the study was to assess the relationship between the position of the sacrum, lumbar and thoracic spine and the mobility of the trunk in the sagittal plane in young women and men. Material and methods: 64 students (33 women and 31 men) were studied. The mean age in the study group was 22.94 ± 1.51 years. The following tests were performed on each subject once: measurement of height and weight, assessment of spinal alignment and mobility in the sagittal plane using Zebris Pointer. Results: The results obtained were analyzed using appropriate statistical tools. Statistically significant correlations were obtained: in the alignment of the sacrum in relation to the lumbar spine (strong correlation), in the alignment of the lumbar spine in relation to the thoracic spine and, in the male group only, between the alignment of the thoracic spine and mobility in the direction of flexion in the thoracic segment (moderate correlation). Conclusions: In women, horizontal sacral alignment coexisting with deepened lordosis was most frequently observed. In addition, women were more likely to have a deepened thoracic kyphosis, less range of motion in the direction of thoracic flexion and extension, and greater mobility in the direction of lumbar flexion and extension than men. In men, the vertical alignment of the sacrum was accompanied by a shallowing of the physiological lordosis. In addition, in this group, a decrease in lordosis influenced an increase in movement to flexion in the thoracic spine. When planning a physiotherapy exercise program for a person in whom abnormalities in the alignment of the lumbopelvic complex have been noted, an individual exercise program should be selected. The study should take into account not only the evaluation of the alignment of the lumbosacral spine, but also the mobility of the segments above and below the examined area taking into account intergender differences.